Molecular simulation on the interaction of Ethinylestradiol (EE2) with polymer membranes in wastewater purification - Bope, Christian Domilongo (2019)
Molecular dynamics (MD) simulations are performed to study the adsorption of solute organic molecules (Ethinylestradiol (EE2) and testosterone) with different polymer membranes such as polyether sulfone (PES), polyvinylidene fluoride (PVDF). The equilibrium MD simulations results for the membrane solution interface system show that the interaction of EE2 with PES is specific and strong, whereas the interaction is weak and non-specific for PVDF. The binding free energies, the non-bonded short range interaction energies and mobility are also consistent with the interaction behaviour found in experiments. The adsorption of testosterone onto PES and PVDF is considered as control system. The result shows that binding free energies of PES and PVDF interacting with organic solute are consistent with experimental result in the order as; PES-EE2 > PES-Testosterone > PVDF-EE2 > PVDF-Testosterone. The formation hydrogen bonds and π–π interactions are observed between the EE2 and PES. In addition, adsorption of EE2 onto polyamide 6-12 (PA612) and polystyrene (PS) membranes are predicted. This simulation study provides molecular insights on the experimental observations and helps as a computational methodology to screen the membrane materials for EE2 removal from wastewater.